Investigating Runner's High: Changes in Mood and Endocannabinoid Concentrations after a 60 min Outdoor Run Considering Sex, Running Frequency, and Age - Theresia Weiermair; Eva Svehlikova; Beate Boulgaropoulos; Christoph Magnes; Anita Eberl (MDPI AG, 2024)
Runner's high is a euphoric emotional state occurring during and post-physical exercise. Although previous data indicate endocannabinoids' involvement in animal runner's high, their role in human runner's high remains to be established. We investigated runner's high in healthy humans assessing mood and plasma endocannabinoid concentration changes pre- and post a 60 min outdoor run, considering sex (8 females/8 males), running frequency (4 occasional/12 regular runners) and age (median split 36 years). Mood, AEA, and 2-AG concentrations were significantly increased post-run considering all participants (p < 0.0001, p < 0.0001, p < 0.01, respectively), with 2-AG varying more than AEA concentrations. Concentrations of both endocannabinoids increased pre- to post-run in women (p < 0.01) but the AEA concentration increase was higher in females than in males (p < 0.05). Post-run concentration increase appeared to be more pronounced in occasional than in regular runners for 2-AG but not for AEA. However, regular runners experienced stronger mood increases and better post-run mood than occasional runners. Post-run endocannabinoid concentrations were increased regardless of age. AEA concentrations and their post-run changes were less affected by running frequency and age than those of 2-AG. These findings provide insights into the interplay of physical exercise, physiological/psychological factors and demographics, laying a valuable foundation for future research.